International investment law and sustainable development - Key cases from the 2010s - SCHACHERER, Stefanie (Institutional Knowledge at Singapore Management University, 2018)
The majority of cases included in this book specifically involve situations in which the allegedly wrongful act of the host state consisted of new legislation adopted as a matter of public policy, such as health, environmental protection, economic development and taxation. Two investment protection standards clash with the regulatory autonomy of host states in most cases: (i) fair and equitable treatment (FET) and the protection of investors’ legitimate expectations and (ii) indirect expropriation. In fact, several cases in this book illustrate once more the broad discretion that many tribunals adopt in circumscribing the regulatory autonomy of states.